PENGARUH NILAI TUKAR, JUMLAH UANG BEREDAR, DAN INDEKS DOW JONES, TERHADAP IHSG - Mawadah, Wihdatul; Effriyanti (Jurnal Riset Terapan Akuntansi, 2025)
The purpose of this study is to determine and obtain empirical evidence regarding the effect of money supply, the Dow Jones Index, and exchange rates on the IHSG (Composite Stock Price Index). This study employs an associative quantitative approach. The population used in this study is data from the Indonesia Stock Exchange (IDX) covering the years 2019 to 2023, namely data on the IHSG, exchange rate, money supply, and Dow Jones Index. This study uses a saturated sample determination technique with a sampling method using a non-probability sampling approach. The data obtained was analyzed using SPSS version 29 data processing software. This study reveals that the Exchange Rate, Money Supply, and Dow Jones Index have a simultaneous effect on the IHSG. Partially, the Exchange Rate and Dow Jones Index have an effect on the IHSG, while the Money Supply does not have an effect on the IHSG Keywords: Exchange Rate, Money Supply, DJIA, IHSG